Simulated responses of global rice trade to variations in yield under climate change: Evidence from main rice-producing countries. (25th January 2021) - Wu, Feng; Wang, Yihan; Liu, Yu; Liu, Yawen; Zhang, Yali
Abstract: Climate change threatens food security and will therefore further challenge sustainable development goals. Bangladesh, China, India, and Myanmar (BCIM), primary rice producers and consumers, have been experiencing the impacts of climate change for decades. This study examines climate-induced changes in BCIM's rice yield from a meta-analysis based on a 1.5 °C climate change scenario and then presents a Global Trade Analysis Project (GTAP) model to simulate the consequent international impacts on rice production, price, trade, and self-sufficiency. Results show that a 1.5 °C scenario will cause a substantial rice yield loss of 5.39%, 12.44%, and 3.87% in China, Bangladesh, and Myanmar, respectively, but will lead to an increase of 8.62% in rice yield in India. Further, global trade responds to climate change, resulting in decreases in paddy and processed rice production for most countries and larger domestic price fluctuations only for BCIM. Rice production loss under a 1.5 °C scenario is dampened through trade to adapt to climate change, especially for China, as its paddy rice production loss (0.30%) is far less than the yield loss (5.39%). BCIM countries will adjust their import and export structure with little change in rice self-sufficiency. This study concludes with policy recommendations to adapt to climate change guiding more open rice trade regimes and developing rice varieties.